A Preliminary Study on Sources of Banding Artifacts for the Identification of Monochromatic Laser Printers1, 2. Issue 6 (16th March 2017) - Liu, Ning; Zhang, Lichao; Chen, Chuntao
Abstract: The analysis of questioned documents printed with monochromatic toner has been a great challenge to document examiners. Banding artifacts, which are often perceived in the outputs of laser printers, could be a solution to the identification of printers. In this study, sources other than the gear transmission errors were discovered for some primary banding frequency components. By detecting the angular velocity variation of photosensitive drums and other rotating parts of the tested printers and comparing them with the banding signals extracted from the printouts, the authors located the sources of banding frequency components. It was shown that the sources of some primary and persistent banding signals, which were previously unknown, were traced to the periodic velocity variations of the motors or the timing belts. As inherent signatures, banding artifacts could be promising features for discriminating documents printed by individual laser printers.